2001
DOI: 10.1063/1.1415536
|View full text |Cite
|
Sign up to set email alerts
|

Reflection second-harmonic microscopy of individual semiconductor microstructures

Abstract: Second-harmonic scanning optical microscopy in reflection is used to image at room temperature individual GaInP/GaAs microstructures formed on a GaAs (001) substrate. Second-harmonic images of individual microstructures are recorded along with first-harmonic images for four combinations of polarizations of the pump and second-harmonic radiation with different pump wavelengths in the range of 720–920 nm. We observe different second-harmonic images for different polarization configurations and their evolution wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For example, the metal−insulator transitions in colloidal Ag nanoparticles and ultrafast phase transitions in GaAs have been observed by monitoring the bulk SHG response. In addition, previous studies of SHG microscopy have elucidated a variety of effects, including changes in carrier dynamics associated with defects and interfaces.…”
mentioning
confidence: 99%
“…For example, the metal−insulator transitions in colloidal Ag nanoparticles and ultrafast phase transitions in GaAs have been observed by monitoring the bulk SHG response. In addition, previous studies of SHG microscopy have elucidated a variety of effects, including changes in carrier dynamics associated with defects and interfaces.…”
mentioning
confidence: 99%
“…SHG microscopy has been successfully used for imaging of periodically poled ferroelectric domains 3,4 , domain structures in epitaxially grown magnetic garnet films 5 , polymer monolayers 6 and polar orientational distribution in thin polymer films 7 . Over recent years, we have successfully employed SH scanning optical microscopy (SHSOM) for imaging of periodically poled ferroelectric domains 8 , domains in polycrystalline metals 9 , poled silica waveguides 10 , semiconductor quantum dots 11 and individual microstructures 12 . The SHSOM apparatus used in these investigations has now been improved with respect to both sample scanning accuracy and pump light focusing.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is known for its high contrast and signal-to-noise ratio of images as compared to ordinary SHG microscopy [14,15], as well as providing additional information about structural properties of the samples [16][17][18]. It was demonstrated that application of this technique to microstructures allows one to separate the SHG contributions from different parts of the structure [19].…”
mentioning
confidence: 99%